2020
DOI: 10.1002/er.5167
|View full text |Cite
|
Sign up to set email alerts
|

Bauxite waste with low Fe 2 O 3 and high Na concentration as a promising oxygen carrier in chemical looping combustion

Abstract: Summary Development of a cost‐effective oxygen carrier (OC) for chemical looping combustion (CLC) technology remains an important task to be accomplished. Bauxite waste red mud from the United States has shown promise as an OC, but bauxite waste from China has not been evaluated extensively although huge quantities of it exists. In comparison, the Chinese bauxite waste usually contains low Fe2O3 and high Na concentration. Hence, the purpose of this study was to evaluate a typical red mud (from Zibo, China) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…During the calcination process, the chemical phases of calcite, boehmite, katoite, cancrinite, sodalite, and gibbsite are decomposed following the reactions (–), with the solid products of Al 2 O 3 , NaAlSiO 4 , Ca 2 Al 2 SiO 7 , and CaO. Na 2 O and CaO could react with Al 2 O 3 to produce Ca 2 Al 2 SiO 7 (), and they also can react with SiO 2 to produce NaAlSiO 4 (). , Ca 2 Al 2 SiO 7 and NaAlSiO 4 from the decompostion reactions (–) and solid–solid reactions ( and ) are stable materials with a high melting point. Sodium after calcination in red mud is in the stable form of NaAlSiO 4 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the calcination process, the chemical phases of calcite, boehmite, katoite, cancrinite, sodalite, and gibbsite are decomposed following the reactions (–), with the solid products of Al 2 O 3 , NaAlSiO 4 , Ca 2 Al 2 SiO 7 , and CaO. Na 2 O and CaO could react with Al 2 O 3 to produce Ca 2 Al 2 SiO 7 (), and they also can react with SiO 2 to produce NaAlSiO 4 (). , Ca 2 Al 2 SiO 7 and NaAlSiO 4 from the decompostion reactions (–) and solid–solid reactions ( and ) are stable materials with a high melting point. Sodium after calcination in red mud is in the stable form of NaAlSiO 4 . …”
Section: Resultsmentioning
confidence: 99%
“…Under high temperature operation, the interaction between Na and inert Si based substances is inevitable, with a subsequent particle agglomeration being one of the biggest concerns in terms of a stable operating CLC process. Liu et al 26 found that Na in red mud exists in the form of NaAlSiO 4 due to the interactions among the substances of Na, Al, and Si in red mud under high calcination temperatures. Further, Bao et al 25 found that Na in red mud could catalyze solid fuel gasification.…”
Section: Introductionmentioning
confidence: 99%
“…The compositional analysis of RM is similar to that of the synthetic OCs, with large amounts of Fe 2 O 3 and inert compounds, such as Al 2 O 3 , SiO 2 , and TiO 2 , and AAEM-containing compounds, such as CaO and Na 2 O. Hence, many studies have been conducted on the use of RM as an OC. More than 90% of the RM is produced by the Bayer process, , and its composition is mainly related to the type of bauxite used and the impurities therein. Generally speaking, bauxite can be divided into types containing gibbsite, boehmite, diaspore, and mixtures thereof.…”
Section: Introductionmentioning
confidence: 84%
“…At present, the traditional gasification methods have the disadvantages of low energy efficiency, high gas production cost, and complex systems. 5,6 In order to improve gas quality and reduce production costs, biomass chemical looping gasification technology is proposed. 7 Biomass chemical looping is an emerging gasification technology.…”
Section: Introductionmentioning
confidence: 99%